The discipline of architecture - Piotrowski, Andrzej; Robinson, Julia W. (University of Minnesota Press, 2001)
The essays collected in this groundbreaking volume address the current state of architecture as an academic and professional discipline. Often critical of the current paradigm, these essays offer a provocative challenge to accepted assumptions about the production, dissemination, and reception of architectural knowledge.